Graduate Student Digital Literacy Promotion Pathway Driven by AIGC - Xuemei LUO, Yuzhe LIN (Nongye tushu qingbao xuebao)
[Purpose/Significance] Artificial intelligence-generated content (AIGC) is having a profound impact on the field of education. Currently, there are some problems in the digital education environment, such as incomplete digital infrastructure and slow digital transformation. The postgraduate education system has not yet fully responded to the changes in the educational environment in the intelligent era. In the era of AIGC, digital literacy has become an important component of graduate students' core competence, which is related to their future academic research and career development. In order to promote graduate students from the understanding of intelligent technology to the rational application, this paper explores a new way of talent training to adapt to the development of intelligent technology. Improving graduate students' literacy skills is important for adapting to the new demands of learning and research in the AIGC era. [Method/Process] Through a literature review and case analysis, this study explores the importance of digital literacy education for postgraduate students, and identifies challenges in educational content and teaching methods. Based on the successful experience of international universities, by analyzing the advantages and application scenarios of AIGC technology, combined with the current situation and existing problems of graduate students' digital literacy education, this paper proposes strategies and ways to improve graduate students' digital literacy. Based on the relevant theories of educational technology development, combined with educational practice and case analysis, this paper proposes an improvement plan for postgraduate students' digital literacy education in the AIGC era. [Results/Conclusions] In order to adapt to the changes brought about by AIGC technology, colleges and universities need to innovate in curriculum design, teaching paradigm and evaluation methods, and put forward strategies such as introducing AIGC-related knowledge modules, building interactive digital resources' intelligent recommendation platform, establishing interdisciplinary integration mechanism, strengthening ethical and legal education and establishing supervision mechanism, so as to promote the comprehensive ability of graduate students. Future research can further explore the deep integration path of AIGC technology and postgraduate students' digital literacy education, the high-order thinking practice direction of AIGC to promote digital literacy, and how to give full play to the positive role of AIGC technology in education while ensuring academic integrity. The shortcoming of this study is that because the development of AIGC technology is still in rapid evolution, some of the suggestions of the study may need to be adjusted in time according to the further development of the technology.